Design and Performance of Archimedes Single Screw Turbine as Micro Hydro Power Plant with Flow Rate Debit Variations (Case Study in Air Dingin, Samadua - South Aceh) - Irwansyah Syam; Muhammad Ilham Maulana; Ahmad Syuhada (Jurnal Inotera, 2019)
Renewable energy is energy derived from nature and can be produced continuously such as water energy as a micro hydropower plant. The development of a micro hydropower plant is to utilize the potential energy of water flow that has a certain head and discharge to be converted by turbines and generators into energy electricity that can be used in the development of Archimedes Single Screw Turbines. Archimedes Single Screw Turbine is a type of turbine that is capable of operating with low head 1-15 meter in river flow and irrigation. Aceh is one of the regions that have a large amount of water energy potential to be used as energy driving water turbines. The purpose of this study is to design, make Turbine Archimedes Single Screw construction and conduct turbine testing and determine the performance of Archimedes Single Screw Turbine based on the effect of water flow discharge on rotation, torque, power, and optimum efficiency so that it can determine the right turbine design and performance well. Archimedes Single Screw turbine is made with 201 stainless steel which has dimensions of N = 1 blade (Ro= 130 mm, Ri = 70 mm) with pitch 2Ro, Turbine length (L = 2 m), head = 1 m, Angle θ = 300. The variables measured and observed are the rotation of the turbine, torque, and flow rate. Tests were carried out on 3 variations of flow rate, namely 0.02 m3/s, 0.009 m3/s, and 0.003 m3/s. The test results, the highest rotation, and turbine power occur at flowrate 0.02 m3/s at 236.40 rpm with a power of 116.10 watts and maximum turbine efficiency is 57%. Thus, the turbine with maximum power and efficiency is obtained when the flow rate is 0.02 m3 /s.